Reusing process patterns in software process models modification. Issue 8 (7th February 2018) - Hachemi, Asma; Ahmed‐Nacer, Mohamed
Abstract: Process patterns offer proven solutions to reuse in process modeling. This reuse can take many forms; however, we are particularly interested in the form where patterns are merged with already existing process models to enrich or to correct them to satisfy certain constraints or to increase their efficiency. We aim through the present work to propose an approach that proceeds the merging automatically. The difficulty is that some conflicts may arise between the pattern being reused and the model being modified, resulting in an incoherent process model. We start this work by studying possible conflicts (especially that of first order), which can be encountered when merging, and then we propose an algorithm ensuring the automatic reuse and managing these conflicts. We highlight through a comparison the benefits of our proposal. The difficulty of patterns reuse to modify existing models gives rise to very few works in the literature. Our approach aims to offer a possible solution that ensures conflicts management. Automating such form of reuse will enhance patterns exploitation within the software community, as well as it will open many perspectives based on process models merging.